Microstructure, chemistry and mechanical properties of Ni-based superalloy Rene N4 under irradiation at room temperature. (15th August 2015) - Sun, C.; Kirk, M.; Li, M.; Hattar, K.; Wang, Y.; Anderoglu, O.; Valdez, J.; Uberuaga, B.P.; Dickerson, R.; Maloy, S.A.
Abstract: Nickel superalloys with cubic L12 structured γ′ (Ni3 (Al, Ti)) precipitates exhibit high strength at high temperatures and excellent corrosion resistance when exposed to water. Unlike prior studies on irradiation damage of other Ni-based superalloys, our study on Rene N4 involves much larger γ′ precipitates, ∼450 nm in size, a size regime where the irradiation-induced disordering and dissolution kinetics and the corresponding mechanical property evolution are unknown. We report that under heavy ion irradiation at room temperature, the submicron-sized γ′ precipitates were fully disordered at ∼0.3 dpa and only later partially dissolved after 75 dpa irradiation. Nanoindentation experiments indicate that the mechanical properties of the alloy change significantly, with a dramatic decrease in hardness, with irradiation dose. Three contributions to the change in hardness were examined: defect clusters, disordering and dissolution. The generation of defect clusters in the matrix and precipitates slightly increased the indentation hardness, while disordering of the submicron-sized γ′ precipitates resulted in a dramatic decrease in the total hardness, which decreased further during the early stages of the intermixing between γ′ precipitates and matrix (<18 dpa). Controlling the long-range-ordering and chemical intermixing can be used to tailor the mechanical properties of Ni-based superalloys under irradiation.